The Influence of Turnover, Motivation, and Compensation on Employee Performance at Permata Hati Hospital Palangka Raya - Christa, Usup Riassy (PT FORMOSA CENDEKIA GLOBAL, 2024)
Research in the field of human resource management at Permata Hati Hospital, which focuses on maternity, maternal and child services, faces challenges in maintaining performance due to employee turnover, motivation and compensation strategies. Turnover, although often seen as a detrimental factor, in certain situations can improve performance if managed well, such as by replacing employees who are unproductive or do not fit the organizational culture. However, negative impacts such as decreased morale, high costs, and operational disruption are often more dominant, especially in hospital environments that require consistency of service. Motivation and compensation are two important aspects that can improve employee performance. Increased motivation through recognition, career development opportunities, and a supportive work environment can increase employee productivity, engagement, and loyalty. Fair compensation, both financial and non-financial, also plays an important role in attracting and retaining quality employees, and encouraging them to achieve optimal performance. In the context of Permata Hati Hospital, implementing motivation and compensation strategies tailored to the specific needs of maternity hospitals, mothers and children can improve overall performance